Project Tutok 3Rs (Reading, Writing, Arithmetic) in Maybancal Elementary School - Tancingco, Hazelann (Journal of Research and Investigation in Education, 2024)
The purpose of this study was to investigate and determine the effectiveness of Project Tutok 3Rs (Reading, Writing, Arithmetic) in improving the performance of grade 4 learners and teacher’s perception in Maybancal Elementary School and SPED Center. This study used quantitative types of research to determine the performance of the learners after the implementation of intervention and tested the significant difference before and after the implementation. This is also a 1ualitative type of research for this determined the perception of the learners after the implementation of intervention and had tested the significant difference on the perception before and after the implementation. The respondents of the study were the Grade 4 learners in Maybancal Elementary School and Sped Center. The study was conducted during the Third Quarter of the school year 2021-2022. Tracking the findings, based from the result on Mean and Paired Sample T-test, the study found that Project Tutok 3Rs increased the performance of the learners where the mean percentage of 82% increased to 90%. It was concluded that in Maybancal Elementary School, Project Tutok 3Rs has a great impact in the improvement of learner’s performances in the school.